Cardiac sequelae of novel coronavirus disease 2019 (COVID-19): a clinical case series. Issue Volume 4:Issue FI1(2020)Special Issue (13th June 2020) - Demertzis, Zachary D; Dagher, Carina; Malette, Kelly M; Fadel, Raef A; Bradley, Patrick B; Brar, Indira; Rabbani, Bobak T; Suleyman, Geehan
Abstract: Background: COVID-19 caused by severe acute respiratory syndrome coronavirus 2 most commonly manifests with fever and respiratory illness. The cardiovascular manifestations have become more prevalent but can potentially go unrecognized. We look to describe cardiac manifestations in three patients with COVID-19 using cardiac enzymes, electrocardiograms, and echocardiography. Case summaries: The first patient, a 67-year-old Caucasian female with non-ischaemic dilated cardiomyopathy, presented with dyspnoea on exertion and orthopnoea 1 week after testing positive for COVID-19. Echocardiogram revealed large pericardial effusion with findings consistent with tamponade. A pericardial drain was placed, and fluid studies were consistent with viral pericarditis, treated with colchicine, hydroxychloroquine, and methylprednisolone. Follow-up echocardiograms showed apical hypokinesis, that later resolved, consistent with Takotsubo syndrome. The second patient, a 46-year-old African American male with obesity and type 2 diabetes mellitus presented with fevers, cough, and dyspnoea due to COVID-19. Clinical course was complicated with pulseless electrical activity arrest; he was found to have D-dimer and troponin elevation, and inferior wall ST elevation on ECG concerning for STEMI due to microemboli. The patient succumbed to the illness. The third patient, a 76-year-old African American female with hypertension, presented with diarrhoea, fever, and myalgia, and was found to be COVID-19 positive. Clinical course was complicated, with acute troponin elevation, decreased cardiac index, and severe hypokinesis of the basilar wall suggestive of reverse Takotsubo syndrome. The cardiac index improved after pronation and non-STEMI therapy; however, the patient expired due to worsening respiratory status. Discussion: These case reports demonstrate cardiovascular manifestations of COVID-19 that required monitoring and urgent intervention.